Production of CO-rich Hydrogen from Methane Dry Reforming Over Lanthania-Supported Cobalt Catalyst: Kinetic and Mechanistic Studies - Ayodele, Bamidele V.; Khan, Maksudur R.; Lam, Su Shiung; Cheng, C. K. (Elsevier, 2016)
In this study, the production of CO-rich hydrogen from methane dry reforming over lanthania-supported Co catalyst was investigated. The Co/La2O3 catalyst was synthesized via wet-impregnation method and characterized using instrument techniques such as TGA, FTIR, XRD, FESEM-EDX and N2 adsorption-desorption analysis. The catalytic activity of the Co/La2O3 catalyst tested in a fixed bed stainless steel reactor yielded highest CH4 and CO2 conversion of 50% and 60% respectively at 1023 K and feed ratio of 1.0. The methane dry reforming reaction gave highest H2 and CO yield of 45% and 58% respectively. Furthermore, kinetics and mechanistic behavior of the La2O3 supported Co catalyst in methane dry reforming reaction was investigated as a function of temperature and partial pressure of reactants (CH4 and CO2). The experimental data obtained from the kinetics measurements were fitted using the empirical power-law rate expression, as well as six different Langmuir-Hinshelwood kinetics models. The six models were then statistically and thermodynamically discriminated. Consequently, the Langmuir-Hinshelwood kinetics model (dual-site associative adsorption of both CH4 and CO2 with bimolecular surface reaction) was adjudged the best representative model. Activation energy values of 96.44 and 98.11 kJ mol1 were obtained for the CH4 consumptions from the power-law and Langmuir-Hinshelwood models, respectively. A lower activation energy of circa 72 kJ mol1 obtained for CO2 consumption showed that the rate of consumption of CO2 consumption was speedier than CH4.